Conduction system pacing improves the outcomes on patients with high percentage of ventricular pacing and heart failure with mildly reduced ejection fraction - Zhang, Duo-duo; Zhao, Fu-lu; Yang, Yi-heng; Ma, Cheng-ming; Ma, Pei-pei; Zhao, Yan-ni; Xia, Yun-long; Gao, Lian-jun; Dong, Ying-xue (Frontiers in Cardiovascular Medicine, 2023)
Aims This study aimed to investigate the efficacy and safety of CSP in patients with a high percentage of ventricular pacing and heart failure with HFmrEF. Methods Patients who underwent CSP for HFmrEF and ventricular pacing >40% were consecutively enrolled from January 2018 to May 2021. All participants were followed up at least 12 months. Clinical data including cardiac performance and lead outcomes were compared before and after the procedure. Left ventricular ejection fraction (LVEF) was measured using the biplane Simpson's method. HFmrEF was defined as heart failure with the LVEF ranging from 41%–49%. Results CSP was successfully performed in 64 cases (96.97%), which included 16 cases of left bundle branch pacing (LBBP) and 48 cases of His bundle pacing (HBP). After a mean of 23.12 ± 8.17 months follow-up, NYHA classification (P < 0.001), LVEF (42.45 ± 1.84% vs. 49.97 ± 3.57%, P < 0.001) and left ventricular end diastolic diameter (LVEDD) (55.59 ± 6.17 mm vs. 51.66 ± 3.48 mm, P < 0.001) improved significantly. During follow-up, more than half (39/64,60.9%) of patients returned to normal LVEF and LVEDD with complete reverse remodeling. The pacing threshold in LBBP was lower (0.90 ± 0.27 V@0.4 ms vs. 1.61 ± 0.71 V@0.4 ms, P < 0.001) than that in HBP. No perforation, electrode dislodging, thrombosis or infection was observed during follow-up. Conclusions CSP could improve the clinical outcomes in patients with HFmrEF and a high percentage of ventricular pacing. LBBP might be a better choice because of its feasibility and safety, especially in patients with infranodal atrioventricular block.